Overnight urinary cortisol and cortisone add new insights into adaptation to training - Gouarne, C.; Groussard, C.; Gratas-Delamarche, A.; Delamarche, P.; Duclos, M. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To examine the effects of training on the HPA axis using two new noninvasive tools: salivary cortisol response to awakening and overnight urinary cortisol and cortisone excretion, and on the sympathoadrenal system using overnight catecholamines excretion. To dissociate the effects of training to those of seasonal hormonal variations, endurance-trained men were compared with sedentary men.